Labor cost and export dynamics in a developing economy: the impact of minimum wage increase on trade margins in Peru - Arcaya Caycho, Jose Gregory (2024)
This research investigates the impact of minimum wage increases on the export performance of firms in Peru. The study explores how varying degrees of exposure to minimum wage hikes, defined by departmental and industry-level classifications, influence key export outcomes such as the propensity to export, export values, the number of markets, and the number of products exported. Utilizing a firm level administrative data, this research employs a difference-in-differences methodology, concluding that firms with higher exposure to minimum wage increases exhibit a significant reduction in their likelihood to engage in export activities. This negative impact is particularly pronounced in formal sectors, where firms are more strictly bound by wage regulations, thereby facing higher labor costs that diminish their international competitiveness. The results include robustness checks, such as placebo and falsification tests, and an event study analysis, to validate the main findings by demonstrating that the negative effects on export propensity and values are indeed a consequence of the 2016 minimum wage hike.